Efektivitas Ekstrak Biji Labu Kuning (Cucurbita) Terhadap Kadar Hemoglobin - Harlinah Harlinah; Corlina M Haumahu (Malahayati Nursing Journal, 2022)
ABSTRACT Pregnant women are susceptible to anaemia which can lead to abortion, premature delivery, inhibition of fetal growth and development in the womb, uncomplicated infection, threat of cord decompensation, premature rupture of membranes, antepartum bleeding, impaired strength to push, postpartum bleeding, uncomplicated infection and anaemia during pregnancy. The purpose of this study was to determine the effectiveness of pumpkin seed extract (Cucurbita) on haemoglobin levels. This type of research is a Quasi Experiment with a pretest-posttest with a control group design. The research sample is women of childbearing age-aged 15-49 years who are willing to be respondents selected using consecutive sampling. Twenty people in each treatment group and control group were divided using a simple random sample. The instrument used in this research is a digital HB meter. Pumpkin (Cucurbita) seed extract for 21 days with a dose of 2x a day. Data analysis used Independent Samples T-Test, N-Gain Score Test and continued with N-Gain Percent. The average results showed that Women of Childbearing Age haemoglobin levels in the treatment group were more significant than in the control group. The Independent Samples T-Test test showed a significant difference between the treatment and control groups, with a P-value of 0.000 P 0.05. So the conclusion from the results of this study is that there is a significant difference. They are giving Pumpkin Seed Extract (Cucurbita) to Increase haemoglobin Levels in Women of Childbearing Age. The data of the N-Gain Test Score shows the effectiveness, with the category value showing a moderate value in the treatment group while the control group shows a value of 0.2 (low). The N-Gain Test Percent test data indicates reasonably practical effectiveness in the treatment group compared to the control group, with a value of 63.5% (quite effective). This study found that pumpkin seeds were quite effective in increasing the haemoglobin levels of women of childbearing age. Pumpkin seeds can be a complementary food for iron (Fe) supplements in women of childbearing age. Keywords: Women of childbearing age, pumpkin seeds, haemoglobin, childbirth ABSTRAK Ibu  hamil  rentan  terkena  anemia yang dapat berdampak  abortus, persalinan prematur, hambatan tumbuh kembang janin dalam rahim, mudah  terjadi  infeksi,  ancaman  dekompensasi kordis,  ketuban  pecah  dini,  dan pendarahan  anterpartum, gangguan kekuatan mengejan, pendarahan    postpartum,    mudah    terinfeksi dan anemia  kala  nifas. Tujuan penelitian ini adalah untuk mengetahui efektivitas ekstrak biji labu kuning (cucurbita) terhadap kadar hemoglobin. Jenis penelitian ini adalah Quasi Experiment dengan rancangan Pretest posttest with control group design. Sampel penelitian ini adalah Wanita usia subur berumur 15-49 tahun yang bersedia menjadi responden dipilih menggunakan consecutive sampling. Sebanyak masing-masing 20 orang kelompok pelakuan dan kelompok control dibagi menggunakan simple random sampling.  Instrumen yang digunakan dalam penelitian ini adalah HB meter digital. Ekstrak biji labu kuning (Cucurbita) selama 21 hari dengan dosis 2x sehari. Analisis data menggunakan Independent Samples T-Test, uji N-Gain Score Test dan dilanjutkan dengan N-Gain Persen. Hasil rerata menunjukan bahwa peningkatan kadar haemoglobin WUS pada kelompok Perlakuan lebih besar dari kelompok control. Uji Independent Samples T-Test menunjukan adanya perbedaan yang bermakna antara kelompok  perlakuan  dan kelompok  control,  dengan  didapatkan nilai value P 0,000 yang P0,05.  Maka kesimpulan dari hasil penelitian ini terdapat perbedaan bermakna. Pemberian Ekstrak Biji Labu Kuning (Cucurbita) Terhadap Kenaikan Kadar HB Wanita Usia Subur (WUS). Dari data Uji N-Gain Test Skor menunjukan adanya keefektifitasan dengan nilai kategori menunjukkan nilai sedang pada kelompok  perlakuan  sedangkan pada kelompok  control,  menunjukkan nilai 0,2 (rendah). Dari data Uji N-Gain Test Persen menunjukan adanya keefektifitasan yang cukup efektif pada kelompok  perlakuan  dibandingkan dengan kelompok  control,  dengan  nilai 63,5% (cukup efektif). Penelitian ini menemukan bahwa biji labu kuning cukup efektif meningkatkan kadar hemoglobin wanita usia subur. Biji labu kuning dapat menjadi makanan pendamping suplemen besi (Fe) pada wanita usia subur. Kata kunci: Wanita usia subur, biji labu, hemoglobin, persalinan